Client-centered management of adhesive capsulitis of the shoulder: an occupational therapy approach - Sahu, Chinmayee; Suar, Durga Sankar; Padhan, Srikanta (International Journal Of Community Medicine And Public Health, 2024)
Adhesive capsulitis, commonly known as frozen shoulder, is a musculoskeletal condition characterized by pain and a significant reduction in shoulder mobility, often leading to substantial impairment in daily activities and occupational performance. Although it is considered self-limiting, the condition can persist for months or even years, necessitating medical and rehabilitative interventions. This comprehensive review focuses on the role of occupational therapy in managing adhesive capsulitis, with an emphasis on client-centered approaches. Utilizing a systematic search of databases such as PubMed, Google Scholar, Scopus, and Cochrane, the review includes high-quality evidence from randomized controlled trials, meta-analyses, and systematic reviews, while excluding case reports and cohort studies. Key interventions highlighted include therapeutic modalities, ergonomic modifications, assistive devices, and comprehensive patient education, all of which contribute to reducing pain, improving functional independence, and enhancing overall quality of life. This evidence provides occupational therapy practitioners with a robust framework for tailoring interventions to meet clients’ specific needs, optimizing therapeutic outcomes, and supporting functional recovery.